-(x-6)-8(4+x)=

Simple and best practice solution for -(x-6)-8(4+x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x-6)-8(4+x)= equation:


Simplifying
-1(x + -6) + -8(4 + x) = 0

Reorder the terms:
-1(-6 + x) + -8(4 + x) = 0
(-6 * -1 + x * -1) + -8(4 + x) = 0
(6 + -1x) + -8(4 + x) = 0
6 + -1x + (4 * -8 + x * -8) = 0
6 + -1x + (-32 + -8x) = 0

Reorder the terms:
6 + -32 + -1x + -8x = 0

Combine like terms: 6 + -32 = -26
-26 + -1x + -8x = 0

Combine like terms: -1x + -8x = -9x
-26 + -9x = 0

Solving
-26 + -9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '26' to each side of the equation.
-26 + 26 + -9x = 0 + 26

Combine like terms: -26 + 26 = 0
0 + -9x = 0 + 26
-9x = 0 + 26

Combine like terms: 0 + 26 = 26
-9x = 26

Divide each side by '-9'.
x = -2.888888889

Simplifying
x = -2.888888889

See similar equations:

| 8x-4y-6y+5x+10= | | -4x+.66=2.3 | | x-5/2-6=x-4/3 | | m/15=9/32 | | -5x^2-14+x^4=0 | | 4x-5(5-x)= | | (-4y+4)-(-3y-8)=2 | | (8+2)(7+(2+4))=X | | V=LWHfrow | | 7-3(5-10)=67 | | (8+2)(7+(2+2))=X | | (5/11)(6) | | 24x+9=18x+3 | | 3x/3=a-1/3 | | t=(.20+2.15)873.36 | | 2x/3-7=5 | | 8x^2+18x-15=20 | | t=(.15+2.15)873.36 | | -4-22v+8=6-6-9v+6v | | 3(5-3v)+9v=28 | | (5x-2)(6x+3)= | | t=(.1+2.15)873.36 | | 10(z+4)-2(z-2)=3(z-2)+4(z-1) | | -32-9y=23 | | 27/21=X/28 | | x^2+128x-256=0 | | t=(.10+2.15)873.36 | | (8x^2-3x^3)-(2x^2-7x^3)= | | t=(0.010+2.15)873.36 | | -16-9y=-24 | | x^3+30x^2-400=0 | | 16-9y=-24 |

Equations solver categories